2020
DOI: 10.1007/s00068-020-01526-7
|View full text |Cite
|
Sign up to set email alerts
|

An increasing trend in geriatric trauma patients undergoing surgical stabilization of rib fractures

Abstract: Purpose The proportion of geriatric trauma patients (GTPs) (age ≥ 65 years old) with chest wall injury undergoing surgical stabilization of rib fractures (SSRF) nationally is unknown. We hypothesize a growing trend of GTPs undergoing SSRF, and sought to evaluate risk of respiratory complications and mortality for GTPs compared to younger adults (18–64 years old) undergoing SSRF. Methods The Trauma Quality Improvement Program (2010–2016) was queried for patients with rib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Conservative treatment consisting of (non)invasive ventilation, pain management and physiotherapy, has long been considered the gold standard for the management of rib fractures [ 4 , 5 ]. Since the development of multiple plating and rib fixation systems, there has been a growing interest in operative treatment, also for elderly patients with rib fractures [ 6 , 7 ]. General indications for operative treatment of rib fractures include, flail chest segment, reduction of pain and disability, chest wall deformity, thoracotomy and open rib fractures [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conservative treatment consisting of (non)invasive ventilation, pain management and physiotherapy, has long been considered the gold standard for the management of rib fractures [ 4 , 5 ]. Since the development of multiple plating and rib fixation systems, there has been a growing interest in operative treatment, also for elderly patients with rib fractures [ 6 , 7 ]. General indications for operative treatment of rib fractures include, flail chest segment, reduction of pain and disability, chest wall deformity, thoracotomy and open rib fractures [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite a recent increase in popularity [12, 14], surgical rib fixation in flail chest remains controversial. While multiple studies have evaluated outcomes and indications for fixation, the conclusions have not been consistent and no randomized controlled trial has shown a true mortality benefit with surgical rib fixation in patients with isolated flail chest.…”
Section: Commentmentioning
confidence: 99%
“…While surgical RF has demonstrated improved patient outcomes in recent studies [7,[11][12][13][14][15][16][17][18][19][20], questions regarding the benefit in the obese trauma patient have remained unanswered. To our knowledge, this is the first study to specifically evaluate outcomes in obese patients undergoing RF for flail chest.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations